Maturity mismatching and its impact on the yield curve - Němec, Petr; Potužák, Pavel; Janíčko, Martin, 1983-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2017)
This diploma thesis deals with a new discord in the Austrian economic theory about the effects of maturity mismatching practiced by banks on the shape of the yield curve and defines the not yet established concept of the natural yield curve. The conflicting contributions of Austrian authors are compared for that purpose. Based on this comparison, a coherent theory of the effects of maturity mismatching is presented in a framework of the loanable funds market. A definition of the natural yield curve is then produced by a synthesis of the above-mentioned findings and the Austrian theory of the natural rate of interest. Theoretical research leads to the conclusion that one form of maturity mismatching inevitably results in an Austrian business cycle. The empirical section examines the question of yield curve´s behavior under the influence of maturity mismatching. An explanation concerning the selected hypotheses and their lack of confirmation is given.
Vedoucí práce: Pavel Potužák
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses